Mechanisms of ohmic contact formation of Ti/Al-based metal stacks on p-doped 4H-SiC - Kocher, Matthias; Rommel, Mathias; Michalowski, Pawel; Erlbacher, Tobias (Materials, 2022)
Ohmic contacts on p-doped 4H-SiC are essential for the fabrication of a wide range of power electron devices. Despite the fact that Ti/Al based ohmic contacts are routinely used for ohmic contacts on p-doped 4H-SiC, the underlying contact formation mechanisms are still not fully under-stood. TLM structures were fabricated, measured and analyzed to get a better understanding of the formation mechanism. SIMS analyses at the Ti3SiC2-SiC interface have shown a significant increase of the surface near Al concentration. By using numerical simulation it is shown that this additional surface near Al concentration is essential for the ohmic contact formation.
CRIS-Team Scopus Importer:2022-01-07
Keywords: 4H-SiC; Ohmic contact; SIMS; Simulation; Ti3SiC2